2022
DOI: 10.1021/acs.jpca.2c06701
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Photoelectron Spectrum of 1-Phospha-2,3,4-triazolate Anion, HCPN3, A Theoretical Approach

Abstract: The first five low-lying electronic states of HCPN 3 are probed through extensive ab initio electronic structure and quantum dynamics studies to reproduce the 193 nm photoelectron spectrum. Vibronic Hamiltonian is constructed and availed for time-dependent (TD) and time-independent (TI) quantum dynamical studies. The presence of numerous conical intersections (CIs) and crossings among electronic states yielded interesting nonadiabatic effects in the photoelectron bands of the overall spectrum. Moreover, the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, in this study, the photodetachment spectra of CAl 3 Si – are theoretically resolved, and the nonadiabatic effects among nearly spaced X̃, Ã, B̃ and D̃, Ẽ bands are unfolded. To address this objective, various methodologies have been proposed in the literature, employing diabatic coupling schemes, including the beyond Born–Oppenheimer (BBO) approach, , direct dynamics (DD) approach, exact factorization (EF) scheme, and vibronic coupling theory (VCT). In our study, we opted for the computationally viable VCT developed by Köppel et al, which has demonstrated success in various photodetachment processes. Under the framework of this methodology, the optimized geometry is obtained first, and later ab initio single-point energy calculations are performed for the first six electronic states of CAl 3 Si (outlined in the Computational and Theoretical Approach Section). Later, these calculated energies were utilized for the determination of the Hamiltonian parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, the photodetachment spectra of CAl 3 Si – are theoretically resolved, and the nonadiabatic effects among nearly spaced X̃, Ã, B̃ and D̃, Ẽ bands are unfolded. To address this objective, various methodologies have been proposed in the literature, employing diabatic coupling schemes, including the beyond Born–Oppenheimer (BBO) approach, , direct dynamics (DD) approach, exact factorization (EF) scheme, and vibronic coupling theory (VCT). In our study, we opted for the computationally viable VCT developed by Köppel et al, which has demonstrated success in various photodetachment processes. Under the framework of this methodology, the optimized geometry is obtained first, and later ab initio single-point energy calculations are performed for the first six electronic states of CAl 3 Si (outlined in the Computational and Theoretical Approach Section). Later, these calculated energies were utilized for the determination of the Hamiltonian parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we have employed the vibronic coupling theory approach, [10][11][12][13][14][15][16] which has been very effective for various photodetachment processes. [17][18][19][20][21][22][23][24][25][26] In this approach, we obtained the optimized geometry followed by ab initio single-point energy calculations (described in the Theory and computational details section) for the first seven low-lying electronic states of Al 6 N À . We used these energies to determine the diabatic vibronic Hamiltonian parameters.…”
Section: Introductionmentioning
confidence: 99%